1983
DOI: 10.1111/j.1365-2648.1983.tb00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐centred nursing care in a multi‐racial society: the relevance of ethnographic perspectives in nursing curricula

Abstract: The aim of the paper is to demonstrate the importance of including cultural dimensions as a fundamental component of nursing curricula and to provide some indications as to how this may be achieved. The concept of 'institutionalized racism' is examined, with reference to the absence of the cultural dimension in nursing education, and it is suggested that nurses, as members of a 'caring profession', should be in the forefront in promoting mutual cultural understanding. The argument for promoting cultural awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…These recommendations support claims for a broader educational curriculum, covering social science areas of sociology, anthropology, politics of healthcare, and psychology of disability as an illness experience ( Burrows, 1983;Mattingly, 1991;McColl, 1994). This educational approach can provide a foundation on which effective cross-cultural care can be built.…”
Section: R Scottmentioning
confidence: 82%
“…These recommendations support claims for a broader educational curriculum, covering social science areas of sociology, anthropology, politics of healthcare, and psychology of disability as an illness experience ( Burrows, 1983;Mattingly, 1991;McColl, 1994). This educational approach can provide a foundation on which effective cross-cultural care can be built.…”
Section: R Scottmentioning
confidence: 82%
“…Tbe findmgs of the study suggest that nurses eanng for ethme-mmonty ehents share many eommon expenenees The degree of eonsistency in the accounts given by respondents was remarkable All respondents referred to their inabibty to give 'total care' They frequently separated eare mto basie or pbysical care and tbe 'talkmg to' or psychological care As there is an mereasmg emphasts m nursing today on standard setting (Kendall & Kitson 1986), it is important that cbents, regardless of their cultural group, should acbeve a good standard of care Many respondents felt that the standard of care given to ethmc-mmonty cbents was not as good as it should have been The reasons ated for this were mainly poor commumcation, a lack of knowledge of cultural differences and a lack of resources In some cases, communication was so poor it was impossible to identify mdividual dient problems at all If ethmc-mmonty cbents are to receive mdividualized care, then an assessment of dient problems must be made Some respondents appeared to accept the inevitability of poor communication and did nothmg to improve it It is difficult to find an explanahon for tbs Forrest (1989) found that, when dients were deemed hard to care for, nurses may expenence feebng of negativity, may distance themselves from the client, and may limit themselves to giving 'physical' or 'routine' care It may be that in these circumstances communication may not be so important Some respondents may have found that they could get by, and this may explam why they did bttle to improve communication It is urgent, therefore, that some attempt is made to develop cultural knowledge in nurse education and that nurses are helped and supported with commumcahon difficulties The inadequate interprehng and dietary resources descnbed by respondents must also be addressed Burrows (1983) argued that the nurse must promote an environment where the values, customs and spintual bebefs of an mdividual are respected The findings of this study suggest that such an environment is not being facilitated withm some pradice settmgs There appeared to be a lack of knowledge about cultural differences and an mabibty by respondents to find out about these differences fi-om cbents Many felt that guidelmes m dimcal areas would help However, without individual assessment, guidebnes would only mcrease stereotypmg of cbents and do bttle to improve care…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 10 years ui nursing there has been a shift in focus from disease-and illness-orientated practice to an onentation that emphasize prevenhon of illness and maintenance of healthy lifestyles (Alderton 1983, Gagnon 1983) There has also t)een a move away from a taskonentated approach to a more systemahc individualized approach to care (Holbngworth 1985) This has been facilitated by the adophon of the nursing process as a system of debvery care (Burrows 1983) Wble the challenge to nurses is to prescnbe care that is geared to mdividual needs. Tuck & Hams (1988) argue that cultural sensihvity IS essential when providing individualized care…”
Section: Orientation Towards Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humanist nursing discourse and multiculturalist models adopted within transcuiturai nursing theory share a fundamental quality, a naive optimism regarding the manner in which imderstanding one's own culture and the culture of others as a rational activity creates a tolerance and respect for others and undermines the 'irrationality' of prejudice. This point is clearly illustrated by Burrows' (1983) positive reference to Gardiner (1966): 'What brings people together or keeps them apart is interest... so long as the interest is genuine, questions of race become irrelevant.' The assumption that being aware of one's own culture and those of others leads inexorably towards the alleviation and potential eradication of 'racial' or ethnically informed conflicts and tensions has come under intense criticism in recent years (Sarup 1991, Troyna 1992, Rattansi 1992.…”
Section: Naive Optimismmentioning
confidence: 99%